Urdu Version of Oxford Knee Score and its Application on Osteoarthritis Knee Patients - Atiq Ur Rehman; Khalil ur Rehman; Shahzad Inam; Muhammad Fahad; Asim Niaz Naqvi; Ibrahim Farooq Pasha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To translate the English version of the Oxford Knee Score into Urdu and then to see the internal consistency and validation with the Visual analogue scale and Numerical rating scale in patients suffering from primary knee osteoarthritis.